PENGARUH PRESEPSI KONSUMEN, STRATEGI PEMASARAN DAN LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK BITTERSWEET DI SURAKARTA - Muhammad Umron Afif; Muhammad Sholahudin (JURNAL LENTERA BISNIS, 2025)
The purpose of this research is to examine the effects of consumer perception, marketing strategy, and halal labeling on product purchase decisions. A quantitative approach is employed in this study. The population under investigation consists of consumers of Bittersweet in Surakarta, and the sampling technique applied is purposive sampling, with a total of 145 respondents. The survey instrument utilized a Likert scale format to collect data. For data analysis, PLS was conducted using SMARTPLS 3.2 software. The PLS-SEM analysis involves two primary components: the Inner model and the Outer model. The findings indicate that consumer perception significantly and positively influences purchasing decisions. Additionally, marketing strategies, including people, process, and physical evidence strategies, show a significant positive impact on purchasing decisions. Furthermore, halal labeling also has a significant and positive effect on purchasing decisions. This research introduces a novel approach by integrating consumer perception with elements of service marketing strategies, namely people, processes, and physical evidence, in the context of analyzing purchasing decisions. The addition of the halal label variable provides religious values ​​that are relevant to the characteristics of consumers in Indonesia. Focusing on Bittersweet products in Surakarta also provides a new perspective, as it is rarely studied in the context of contemporary desserts. The combination of these variables is still rarely studied simultaneously, thus providing significant theoretical and practical contributions.